ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Toifatul Hanik, 12.05.52.0138; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to determinate the effect of profitability, leverage, liquidity, size, growth, cash position, invesment oppportunity set, managerial ownership on the dividen policy of manufacturing companiesin indonesia stock exchang. This study used quantitative research is to use the indonesia capital market directory manufacturing companies in indonesia stock exchange during the periode 2012-2014 and found 144 companies, while only 22 companies that qualify. The sampling method in this study using purposive sampling ans using regression analysis techniques berganda.Â Based on the result of the analysis showed that the profitability, growth, cash position, Invesment opportunity set but no significant positive effect on dividen policy. Liquidity and managerial ownership but no significant negative effect on dividen policy. Leverage negative and significant effect on dividen policy. Size positive and significant effect on dividen policy. Keywords: Dividen Policy, Profitabolity, Liquidity, Leverage, Size, Growth, Cash Potition, invesment Opportunity Set, Managerial Ownership